Potential pre-activation strategies for improving therapeutic efficacy of mesenchymal stem cells: current status and future prospects - Li, Meirong; Jiang, Yufeng; Hou, Qian; Zhao, Yali; Zhong, Lingzhi; Fu, Xiaobing (Stem cell research & therapy, 2022)
Mesenchymal stem cell (MSC)-based therapy has been considered as a promising approach targeting a variety of intractable diseases due to remarkable multiple effect of MSCs, such as multilineage differentiation, immunomodulatory property, and pro-regenerative capacity. However, poor engraftment, low survival rate of transplanted MSC, and impaired donor-MSC potency under host age/disease result in unsatisfactory therapeutic outcomes. Enhancement strategies, including genetic manipulation, pre-activation, and modification of culture method, have been investigated to generate highly functional MSC, and approaches for MSC pre-activation are highlighted. In this review, we summarized the current approaches of MSC pre-activation and further classified, analysed the scientific principles and main characteristics of these manipulations, and described the pros and cons of individual pre-activation strategies. We also discuss the specialized tactics to solve the challenges in this promising field so that it improves MSC therapeutic functions to serve patients better.